Socioeconomic Differences in Sympathovagal Balance: The Healthy Life in an Urban Setting Study. Issue 1 (January 2021) - van Nieuwenhuizen, Benjamin P.; Collard, Didier; Tan, Hanno L.; Blom, Marieke T.; van den Born, Bert-Jan H.; Kunst, Anton E.; van Valkengoed, Irene G.M.
ABSTRACT: Objective: Alterations in sympathovagal balance are associated with cardiovascular disease. If sympathovagal balance differs across socioeconomic groups, it may reflect a mechanism through which disparities in cardiovascular disease occur. We therefore assessed the association between education and occupation with measures of sympathovagal balance in a large multiethnic sample. Methods: We included cross-sectional data of 10, 202 South Asian Surinamese, African Surinamese, Ghanaian, Turkish, Moroccan, and Dutch-origin participants from the Healthy Life in an Urban Setting study. Sympathovagal balance was measured by baroreflex sensitivity (BRS) and the standard deviation of the interbeat interval, calculated from changes in blood pressure and interbeat intervals, from 5-minute recordings. We calculated geometric means and estimated the relative index of inequality, using age- and ethnicity-adjusted linear regression, to quantify the association between education and occupation and sympathovagal balance. In addition, we assessed whether the association was consistent across ethnic groups. Results: The geometric means of BRS ranged from 8.16 ms/mm Hg (confidence interval [CI] = 7.91–8.43 ms/mm Hg) in low-educated to 14.00 ms/mm Hg (CI = 13.53–14.48 ms/mm Hg) in highly educated women, and from 8.32 ms/mm Hg (CI, 7.97–8.69 ms/mm Hg) in low-educated to 12.25 ms/mm Hg (CI = 11.86–12.66 ms/mm Hg) in highly educated men. High education and occupation were statistically significantly associated with higher BRS and standard deviation of the interbeat interval. Compared with the participants of Dutch origin, a pattern of weaker associations was found in the Surinamese and Ghanaian ethnic groups, but not the Turkish and Moroccan groups. Conclusions: There is a clear socioeconomic gradient in measures of sympathovagal balance, indicating that sympathovagal balance may play a role in socioeconomic disparities in cardiovascular morbidity and mortality. Abstract : Supplemental digital content is available in the text.